PENGARUH LIKUIDITAS, KEBIJAKAN DIVIDEN TERHADAP KINERJA KEUANGAN - Putri Maharani; Putri Abella; Nathan Bari Harahap (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This research was conducted with the aim of determining the effect of liquidity and dividend policy on financial performance using food and beverage companies listed on the Indonesia Stock Exchange (BEI) in the period 2021 to 2023. The type of research used is quantitative research. The sampling method used was purposive sampling, namely selecting samples using predetermined criteria. Based on the purposive sample method, there were 23 food and beverage companies listed on the Indonesia Stock Exchange (BEI) with 69 data for 3 years. The data used in this research is an annual report. liquidity is measured by the Current Ratio (CR), dividend policy is measured by the dividend payout ratio (DPR), financial performance is measured by Return On Assets (ROA). Analysis of this research data uses descriptive statistical analysis, Heteroscedasticity Test, Multicollinearity Test. The data was processed using the SPSS 26 application. The results of this research show: H1: Liquidity has an influence on financial performance, H2: Dividend policy has a positive influence on financial performance. Keywords: Liquidity,  Dividend Policy, Financial Performance